Digitalization and Transparency of Waqf Lands Certification: A Strategy to Enhance Public Trust from an Islamic Ethical Perspective - Siti Maghfiroh; Dwi Puspitasari; Lydiawaty binti Hassan Busry (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2026)
Digitalization and transparency have become central issues in modern waqf management. Limited access to clear information on waqf certification and asset management often creates public doubt and weakens institutional trust. This study examines how digitalization and transparency enhance the credibility of waqf certification while being reinforced by Islamic ethical principles. Using a qualitative literature review approach, this research analyzes scholarly works on waqf digitalization, certification systems, and Islamic ethics. The findings show that digital technologies such as centralized digital records, online reporting platforms, real-time tracking systems, and blockchain-based registration can improve accountability, reduce administrative errors, prevent data manipulation, and strengthen public trust. Practically, this study offers a governance-based framework applicable to waqf institutions and regulators, including integrated certification databases, transparent financial dashboards, and technology-based audit mechanisms to ensure legal certainty and institutional credibility. The originality of this research lies in its integrative perspective: it connects digital governance mechanisms with Islamic ethical values. Unlike prior studies that focus mainly on technological or financial aspects, this study positions justice (?adl), honesty (sidq), and transparency (shafaafiyyah) as normative foundations for building a credible, accountable, and ethically grounded waqf certification system.